2022
DOI: 10.29303/jppipa.v8i6.2173
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Practicum-Based LKM Can Improve Concept Understanding in Science Subject Energy Materials

Abstract: Penelitian ini merupakan penelitian pengembangan sebuah bahan ajar berbasis praktikum yang bertujuan untuk mengetahui  jika penggunaan lembar kerja mahasiswa berbasis praktikum dapat meningkatkan pemahaman konsep pada materi energi mata kuliah IPA. LKM atau lembar kerja mahasiswa adalah salah satu contoh media pembelajaran yang sering dipergunakan dalam kegiatan belajar mengajar. Metode yang dipergunakan dalam penelitian yaitu Pre-eksperimen dengan One-Group Pretes-Posttest Design. Dari hasil uji diperoleh has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…It was further explained that students will be skilled in carrying out practicums if students know practicum tools, including tool names, functions, how to use them, and basic skills in using practicum tools; enthusiasm, based on the results of interviews with biology teachers and students, information was obtained that practicum activities are very rarely carried out so that these activities become very interesting which causes to become enthusiastic and motivated to carry out practicum seriously (Väätäjä, 2023). According to Munfaida et al (2022), one of the reasons why science practicum activities are important is that they can generate motivation to learn science. Apart from that, in (Soykurt, 2010;Ni Kadek Nilawati et al, 2023), research, the results of student responses in carrying out practicum were also found to be in a good category.…”
Section: Resultsmentioning
confidence: 99%
“…It was further explained that students will be skilled in carrying out practicums if students know practicum tools, including tool names, functions, how to use them, and basic skills in using practicum tools; enthusiasm, based on the results of interviews with biology teachers and students, information was obtained that practicum activities are very rarely carried out so that these activities become very interesting which causes to become enthusiastic and motivated to carry out practicum seriously (Väätäjä, 2023). According to Munfaida et al (2022), one of the reasons why science practicum activities are important is that they can generate motivation to learn science. Apart from that, in (Soykurt, 2010;Ni Kadek Nilawati et al, 2023), research, the results of student responses in carrying out practicum were also found to be in a good category.…”
Section: Resultsmentioning
confidence: 99%
“…Practicum is a method for teachers to increase students' interest and attention (Adelia et al, 2023). With the practical method, students become trained in conducting experiments so that they will increase their scientific literacy (Munfaida et al, 2022). In line with the opinion of Lestari et al (2021) that practicum is one of the factors that influences student learning outcomes which plays an important role in supporting the success of the science teaching and learning process.…”
Section: Introductionmentioning
confidence: 99%